Plagas que atacan granos de frijol almacenados - Schoonhoven, Aart van (United Nations Development Programme, 1985)
The biology of the insects Acanthoscelides obtectus and Zabrotes subfasciatus attacking stored beans is briefly described. Cultural and chemical control measures are indicated. (CIAT)